The effect of using the soppa application on cognitive and psychomotor improvement of breastfeeding mothers - Ernawati, Ernawati; Widyastuti, Deny Eka; Rohmatika, Dheny; Apriani , Arista; Putri A G, Anggi; Umarianti, Tresia (International Journal of Health Science and Technology, 2023)
Breast care during the puerperium can flex and strengthen the nipples, stimulate milk production, and keep the breasts clean, especially the nipples. The process of lactation, or breastfeeding, is the process of forming breast milk, which involves the hormones prolactin and oxytocin. Breastfeeding needs to be learned, among other things, by learning how to hold the baby so that he can suckle properly and adjust the body position so that he feels comfortable during breastfeeding. Often, breastfeeding failures are caused by incorrect positioning and attachment of the baby. The nipples become chafed so that the mother is reluctant to breastfeed, milk production decreases, and the baby becomes too lazy to suckle. The aim is to find out the effect of using the Soppa application (Simulation Oxytocin Planned Parenthood by Android) on the cognitive and psychomotor improvement of breastfeeding mothers. This type of research is quantitative with a quasi-experiment research design. The research design used a pre- and post-test without a control group design. This study wanted to know about cognitive and psychomotor changes in breastfeeding mothers and family planning using the SOPPA application. The results of the Wilcoxon test obtained a p-value of 0.0001, so H0 was rejected, which means that there is an effect of using the Soppa application (Simulation Oxytosin Planned Parenthood by Android) on the cognitive and psychomotor improvement of breastfeeding mothers.